2019
DOI: 10.1002/mrm.28095
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time MR elastography for viscoelasticity quantification in skeletal muscle during dynamic exercises

Abstract: Purpose To develop and test real‐time MR elastography for viscoelastic parameter quantification in skeletal muscle during dynamic exercises. Methods In 15 healthy participants, 6 groups of lower‐leg muscles (tibialis anterior, tibialis posterior, peroneus, extensor digitorum longus, soleus, gastrocnemius) were investigated by real‐time MR elastography using a single‐shot, steady‐state spiral gradient‐echo pulse sequence and stroboscopic undersampling of harmonic vibrations at 40 Hz frequency. One hundred and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Single-frequency rt-MRE using a 2D single-shot gradient echo MRE pulse sequence with spiral readout was recently introduced for directly mapping skeletal muscle function ( Schrank et al, 2020a ). For rt-MMRE we used a similar prototype—a single-shot, gradient-echo sequence with dual-density spiral readout, which samples multifrequency vibrations in a stroboscopic fashion as illustrated in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Single-frequency rt-MRE using a 2D single-shot gradient echo MRE pulse sequence with spiral readout was recently introduced for directly mapping skeletal muscle function ( Schrank et al, 2020a ). For rt-MMRE we used a similar prototype—a single-shot, gradient-echo sequence with dual-density spiral readout, which samples multifrequency vibrations in a stroboscopic fashion as illustrated in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The same ROI was also used to determine magnetization signal-to-noise ratio (SNR) and wave displacement SNR (WSNR) for every time frame. WSNR was derived using the blind noise estimation method proposed by Donoho et al (1995) as outlined and previously applied to MRE data in Bertalan et al (2019b) and Schrank et al (2020a) This noise estimation method is suited for wave image analysis since the spatial frequencies of MRE waves and noise are well separated in the wavelet domain ( Selesnick et al, 2005 ; Barnhill et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, MRE has demonstrated to detect mechanical property changes of the disc, with shear stiffness measurements having shown to highly correlate with intervertebral disc degeneration [68]. Preliminary phantom and in vivo studies showed the feasibility of this technique to assess mechanical and functional properties of skeletal muscles under passive (rest) conditions [69] and after activation with dynamic exercises [70]. This data might be used as a reference in future studies on muscle disorders in addition to other quantitative MR imaging biomarkers of muscle structure and function [71].…”
Section: Mri/ultrasound Elastographymentioning
confidence: 99%